Early Invasive Versus Ischemia-Guided Strategy in Non-ST-Segment Elevation Acute Coronary Syndrome With Chronic Obstructive Pulmonary Disease: A National Inpatient Sample Analysis. (April 2020) - Ando, Tomo; Adegbala, Oluwole; Takagi, Hisato; Afonso, Luis; Briasoulis, Alexandros
Chronic obstructive pulmonary disease (COPD) is a risk factor for non-ST-segment elevation–acute coronary syndromes (NSTE-ACS). Whether early invasive strategy (EIS) or ischemia-guided strategy (IGS) confers better outcomes in NSTE-ACS with COPD is largely unknown. Nationwide Inpatient Sample database of the United States was queried from 2010 to 2015 to identify NSTE-ACS with and without COPD. Early invasive strategy was defined as coronary angiogram with or without revascularization on admission day 0 or 1, whereas IGS included patients who did not receive EIS. Standardized morbidity ratio weight was used to calculate the adjusted odds ratio. A total of 228 175 NSTE-ACS admissions with COPD were identified of which 34.0% received EIS. In-hospital mortality was lower with EIS in patients with COPD (3.1% vs 5.5%, adjusted odds ratio 0.57, 95% confidence interval 0.50-0.63) compared to IGS, but the magnitude of mortality reduction observed in EIS in patients with COPD was less compared to non-COPD patients ( P interaction = .02). Length of stay was shorter (4.2 vs 4.7 days, P < .0001) but the cost was higher (US$23 804 vs US$18 533, P < .0001) in EIS in COPD. Early invasive strategy resulted in lower in-hospital mortality and marginally shorter length of stay but higher hospitalization cost in NSTE-ACS with COPD.